IDENTIFICATION OF DIFFERENTLY METYLATED GENES POTENTIALLY RELATED TO HUMAN ATHEROSCLEROSIS - M. S. Nazarenko; А. V. Markov; Yu. A. Koroleva; А. A. Sleptsov; А. N. Kazantsev; О. L. Barbarash; V. P. Puzyrev (Российский кардиологический журнал, 2017)
Aim. Identification of the genes, different in the level of DNA methylation among the cells  of intact  or  atherosclerotic arteries  in patients  with coronary  and  carotid atherosclerosis.Material and methods. Into the study group, atherosclerosis patients  were included, who had undergone coronary bypass  surgery or carotid endarterctomy, and relatively healthy individuals. The assessment of methylation level of various 27578  CpG-sites/14475  genes   was  done  with the  microchip  Infinium Human Methylation27 BeadChip (Illumina) in the specimens of atherosclerotically changed coronary (n=6), carotid (n=6), intact internal thoracal arteries (n=8) and large saphenous veins (n=8). Level of methylation in the locus 2q31.1 (HOXD4/HOXD3/MIR10B)  was  measured with bisulphite  pyrosequencing of DNA in the  vessels specimens and leucocytes  of the same  patients  (n=130), as in the leucocytes  of relatively healthy men (n=110).Results. In the cells of atherosclerotically  changed arteries,  comparing  to intact vessels,  the change  of methylation level by 20% and more is found for 46 CpG-sites/42 genes  (pFDR <0,05).  Of those  8 genes  (TLR4,  TRAF1,  ABCB11,  NPR2, ALOX12, TMEM182, ALX4 и FABP1) are known candidates for atherosclerosis or its risk factors by the results of genetics  studies.  Most number of CpG sites, where the highest  decrease of methylation found in the cells of atherosclerotically  changed arteries  comparing  to the intact, were located  in the locus 2q31.1,  with the genes HOXD4/HOXD3/MIR10B. In leucocytes  of patients the level of methylation of one of the  CpG-sites   in  locus  2q31.1   (HOXD4/HOXD3/MIR10B)  higher  in  smokers (18±5%), than non-smokers (14±6%; p<0,05),  and level of methylation of one of CpG-sites in this area of genome is lower in those who had previous ischemic stroke (18±8%) comparing to those with no stroke anamnesis (20±7%; p<0,05).Conclusion. Lowest part of the identifiable differently methylated genes  among the cells of lesioned  arteries  and intact vessels  is related  to atherosclerosis or its risk factors  as a result of genetic  studies  on genetic  associations. It is found that the change of methylation level in locus 2q31.1 (HOXD4/HOXD3/MIR10B) is associated with atherosclerotic lesion of arteries,  and in leucocytes  of patients  the grade  of methylation in the studied  region of genome  is related  to smoking and ischemic stroke.